2013
DOI: 10.1007/s10620-013-2899-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting an Early and Substantial Increase in Mean Arterial Pressure Is Critical in the Management of Type 1 Hepatorenal Syndrome: A Combined Retrospective and Pilot Study

Abstract: Using an early and substantial increase in MAP as a therapeutic target is associated with favorable clinical outcomes in the management of type 1 HRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…Moreover, our findings demonstrate a significant correlation between the magnitude of the increase in MAP and improvement in kidney function during either midodrine/octreotide or norepinephrine therapy for hepatorenal AKI. These results are in agreement with previous reports demonstrating a relationship between MAP gain and renal outcomes [2022,30]. Because our findings were generated from a large number of data points per patient and from close examination of a wide range of MAP changes, the signal detected was robust and strengthens the notion of MAP gain as a therapeutic target.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, our findings demonstrate a significant correlation between the magnitude of the increase in MAP and improvement in kidney function during either midodrine/octreotide or norepinephrine therapy for hepatorenal AKI. These results are in agreement with previous reports demonstrating a relationship between MAP gain and renal outcomes [2022,30]. Because our findings were generated from a large number of data points per patient and from close examination of a wide range of MAP changes, the signal detected was robust and strengthens the notion of MAP gain as a therapeutic target.…”
Section: Discussionsupporting
confidence: 92%
“…However, that relationship seemed lost after adjustment for serum bilirubin. Others have shown that a MAP gain > 10 mmHg might be associated with a positive renal outcome [30,45]. Moreover, clinical trials assessing the use of norepinephrine have been designed to target a rise in MAP of 10 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…A systemic review of randomized controlled studies has indicated that vasoconstrictor therapy of HRS improves short-term patient survival [8]. Prolonged transplant-free survival could also be achieved by the use of such combination therapy via targeting an early and sustained increase in MAP as shown in our recent studies [9,10]. The advent of pharmacological treatment led to renewed interest in RRT as a supportive modality for patients with HRS, either as a bridge to liver transplantation or modality to possibly improve long-term survival without transplantation.…”
Section: Introductionmentioning
confidence: 85%
“…Indeed, systemic review of randomized controlled studies has indicated that vasoconstrictor therapy of HRS improves HRS patient survival [8]. Currently, treatment with combined vasoconstrictors and albumin in patients with HRS has been considered either as a bridge to liver transplantation or modality to possibly improve long-term survival without transplantation [9]. Renal replacement therapy is being used more frequently in such patient populations, but the clinical outcomes are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In one randomized unblinded pilot study, albumin was compared to hetastarch in patients with SBP. 56 Several pharmacological agents have been used in the management of HRS. 52 However, the current evidence suggest that the use of hydroxyethyl starch (HES) increases the risk of AKI and mortality.…”
Section: Managementmentioning
confidence: 99%